GAYA KEPEMIMPINAN KEPALA SEKOLAH DALAM MENINGKATKAN MOTIVASI KERJA TENAGA KEPENDIDIKAN - Fadilah, Rahmi; Ose, Fitria; Idris, Idris; Nellitawati, Nellitawati; Yahya, Yahya (STKIP Pesisir Selatan, 2024)
The principal is the highest leader in an educational institution, has an important role in increasing the work motivation of educational staff. Leadership is the key to effective educational implementation. School principals can lead schools towards improving quality and service by choosing the right leadership style. This research examines the leadership style of school principals to increase the work motivation of educational staff. This research uses a systematic literature review. The results of this research are that the school principal's leadership style on the performance of educational staff has a big influence which includes several aspects of the principal's leadership style, namely: (a) the daily behavior of the principal shows an attitude that is caring, open, cheerful, firm, wise, disciplined and committed, as well as stable emotions; (b) assignments are distributed fairly and instructions are provided; (c) decision making is carried out collectively or jointly; and (d) appropriate and consistent supervision. To improve the performance of educational staff, school principals motivate by providing incentives and giving awards.